2022
DOI: 10.1021/acscatal.2c01358
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Structured Fe–N–C Catalysts with Enriched Iron Sites in Surface Layers for Proton-Exchange Membrane Fuel Cells

Abstract: Carbon-supported and nitrogen-coordinated single iron site materials (denoted as Fe−N−C) are the most promising platinum group metal (PGM)-free cathode catalysts for the oxygen reduction reaction (ORR) because of their encouraging activity and continuously improved stability. However, current Fe−N−C catalysts derived from zeolitic imidazolate framework-8 (ZIF-8) nanocrystal precursors via thermal activation at high temperatures often suffer from low accessible Fe sites because the most active sites are buried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 70 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…25 As shown in Fig. S6, † the results demonstrated that the Co/Ru SAs-N-C possesses a larger BET surface area and higher pore volume than Co SAs-N-C and Ru SAs-N-C, 26 which could provide more paths to transfer gas and electrons. Moreover, EDS revealed that most Zn elements in the three catalysts were evaporated, and the carbon element could be accounted for in all samples, i.e., all samples were adequately carbonised (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…25 As shown in Fig. S6, † the results demonstrated that the Co/Ru SAs-N-C possesses a larger BET surface area and higher pore volume than Co SAs-N-C and Ru SAs-N-C, 26 which could provide more paths to transfer gas and electrons. Moreover, EDS revealed that most Zn elements in the three catalysts were evaporated, and the carbon element could be accounted for in all samples, i.e., all samples were adequately carbonised (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The calcined ZIF-90 successively showed that the specific surface area had increased, which was also caused by the volatilization of zinc and the removal of NaCl after pyrolysis (Figure S2d–i). The combined HRTEM and STEM-EDS analysis showed that the atomic percentage of Fe in Fe 3 C-FeSA@3DCN was as high as 4.36%, and the loading was larger than almost all reported Fe-based catalysts. ,, The aberration-corrected-HAADF–STEM (AC-HAADF-STEM) images in Figure a–c show high-resolution images of Fe 3 C-FeSA@3DCN. Figure a clearly shows the lattice fringes of the graphitic carbon layer (002).…”
Section: Resultsmentioning
confidence: 94%
“…The combined HRTEM and STEM-EDS analysis showed that the atomic percentage of Fe in Fe 3 C-FeSA@3DCN was as high as 4.36%, and the loading was larger than almost all reported Fe-based catalysts. 17,20,36 The aberration-corrected-HAADF− STEM (AC-HAADF-STEM) images in Figure 2a−c show high-resolution images of Fe 3 C-FeSA@3DCN. Figure 2a clearly shows the lattice fringes of the graphitic carbon layer (002).…”
Section: Resultsmentioning
confidence: 99%
“…The 2%Fe-ZIF@NaCl and 2%Fe-ZIF samples involved five different N groups, which included oxidized N at 403.5 eV, graphite N at 401.9 eV, pyrrole N at 400.9 eV, M–N x at 399.8 eV, and pyridine N at 398.5 eV. 34 The position of M–N x was determined by both Fe–N x and Zn–N x structures and the location of the envelope peak of M–N x further indicated the existence of Zn–N x and Fe–N x structures. Pyrrole N and pyridine N were considered as the key to bind to Fe species, facilitating the formation of Fe–N x sites and accelerating 4-electron transfer in the ORR process.…”
Section: Resultsmentioning
confidence: 99%